Changes in Community Integration From Pre- to Post-incarceration: The Influence of Psychological and Criminal Justice Factors. (July 2018) - Moore, Kelly E.; Gregorian, Mariam J.; Tangney, June P.; Folk, Johanna B.; Stuewig, Jeffrey B.; Salatino, Andrew C.
Research on changes in community integration from pre- to post-incarceration has primarily focused on employment and is mixed, showing both deterioration and improvement. Research is needed to examine change in other areas, as well as predictive individual-level factors. We assessed changes in jail inmates' ( n = 334) employment, source of income, residential stability, marital status, and volunteerism from pre- to post-incarceration, and analyzed individual-level predictors of change. On average, more inmates improved than deteriorated in community integration, with education and low criminal thinking predicting the greatest improvement. Across multiple areas, inmates' community integration does not appear to deteriorate from pre- to post-incarceration. Apparent improvements may reflect that people become incarcerated during times of crisis, regressing to baseline by 1 year postrelease.